RELATIONSHIP BETWEEN GENERAL HEALTH AND SLEEP QUALITY IN PATIENTS WITH HIV AND ADDICTS TREATED WITH METHADONE: Life Sciences-Genetics - MOHAMAD HOSSEIN KHOSROPANAH; REZA POURAIEN; AFSANEH NEZHADHOSSEINI; AMIN DINARVAND; MIR FARHAD GHALABANDI; MOHAMAD HOSSSEIN TAGDICE; MEHRDAD HASHEMI (International Journal of Life Science and Pharma Research, 2022)
Health is an important factor in the progress , improvement and well-being of society. Mental health is a dimension of health. Addiction is a physico-psychological condition which threatens the health of individual, family and society due to its progressive nature in all aspects of life. AIDS or Acquired Immunodeficiency Syndrome is a neural-general fatal disorder which is associated with infection with retroviridae virus. Sleep disorder is often an early symptom of a mental illness. Considering the high prevalence of psychiatric disorders among addicted patients and patients with HIV positive, this study was conducted to determine the type of health services among these two groups. This was a cross-sectional, descriptive-analytic research. The studied population included 60 patients with HIV and 300 addicts treated with methadone. Data were collected by 28-item General Health Questionnaire (GHQ-28) and Pittsburgh Sleep Quality Index (PSQI). Data were analyzed by SPSS-11 (p<0.05). The Mann-Whitney test showed a significant relationship between patients and their four mental disorders. Chi-square test showed a significant relationship between patients and impaired sleep quality (p<0.001). Impaired sleep quality was high in both groups and more than three-quarters of the patients complained of this disorder. AIDS and addiction increases the risk of four mental disorders (psychosomatic, anxiety, social dysfunction and depression) and impaired sleep quality. Therefore, preventive measures could be made possible and proper treatment can significantly reduce or prevent these disorders.